Laccase‐Catalyzed Dimerization of Piceid, a Resveratrol Glucoside, and its Further Enzymatic Elaboration. Issue 8 (15th May 2015) - Gavezzotti, Paolo; Bertacchi, Federica; Fronza, Giovanni; Křen, Vladimír; Monti, Daniela; Riva, Sergio
Abstract: The laccase‐catalyzed oxidation of piceid, the 3‐β‐D ‐glucopyranosyl derivative of the stilbenic phytoalexin resveratrol, allowed isolation of the corresponding β‐5 like trans ‐dehydrodimer in good yield (45%) avoiding chromatography. This compound was then submitted to the action of a small library of commercially available hydrolases. While the cellulase from Trichoderma viride was able to fully hydrolyze the diglycosylated dimer to give the corresponding β‐5 like trans ‐dehydrodimer of resveratrol, the β‐glucosidase from almonds allowed the isolation of a monoglycosylated intermediate in reasonable yield. The diastereoisomers and the enantiomers of the isolated dimeric products were separated using a semi‐preparative chiral column. The basic antioxidant properties of these new dimers have been determined. Abstract :